In Vitro and In Vivo Improvement of Islet Quality and Transplantation Successes following Islet Treatment with Biomaterials in Diabetic Rats - Marzieh Nemati; Zahra Ebrahimi; Narges Karbalaei; Sanaz Dastghaib; Sara Khakshournia; Mojtaba Sargazi (Journal of Diabetes Research)
Background. Loss of islet survival and function, caused by native niche disruption and oxidative stress induction during mechanical and enzymatic isolation, limits the effectiveness of islet transplantation. Reconstitution of islet microenvironment, vascularization, and decreased oxidative stress with biomaterials may improve islet quality and graft outcomes. We investigated effects of two biomaterials, platelet-rich plasma and pancreatic islets homogenate combination on islet recovery and quality by evaluating in vitro islet survival, secretory function, and oxidative stress parameters and assessing in vivo transplantation outcomes. Methods. In vitro, islet viability and secretory function of isolated islets were assessed after 24 h and 72 h incubation with biomaterials. Also, oxidative stress markers were measured once after isolation and 24 h after incubation with biomaterials. For evaluating in vivo effects, cultured islets for 24 h were transplanted into subscapular space of diabetic rat kidney, and outcomes were analyzed by measuring serum glucose and insulin concentrations, glucose tolerance test, level of oxidative parameters, and pancreatic gene expression. Results. Treating islets with biomaterials significantly increased their viability and secretory function, reduced MDA level, and elevate SOD and CAT activity. Decreased level of glucose and MDA improved insulin level, increased SOD activity, and also enhanced pdx1 and insulin gene expression in diabetic rats after islet transplantation. Conclusions. Biomaterials used in the present study should be consider as beneficial materials for increasing islet transplantation outcome. These materials may hamper transplantation limitation to some extent.